Implementación de la Dibujoterapia como apoyo emocional a niños de la Fundación Jóvenes contra el Cáncer : Implementation of Dibujoterapia as emotional support to children of the Young Foundation against Cancer (La U Investiga, 2018)
Cancer is a result of uncontrolled growth of unusual cells that originate in the body, which tend to live longer compared to normal cells and as a consequence tumors may appear and destroy close parts of the area; This diagnostic affects both, the person who suffers and the family, affecting their quality of life. This research carried out by students of the Physical Therapy career was made in Fundación Jóvenes Contra el Cáncer who every day provide an emotional support to the members and their families; This Foundation is composed of a large number of vulnerable people who suffer various physical and emotional discomforts and above all struggle to survive despite all the adversities present. That is why we have opted for the elaboration of toys in cloth for children of said Foundation in order to promote their creativity and psychomotricity favoringthem emotionally. It began by conducting a survey of the children’s representatives including important parameters for the manufacture of the doll, in addition this survey consisted of a space for the child to capture some favorite character or his imagination using pencil and colors. These surveys were useful to distinguish areas in our population thanks to the analysis of the results. After having made these dolls, the implementation of this research was carried out in which the fabric doll that the child drew on the sheet of paper was presented.
Keywords: Cancer; foundation; children; health; toys